2019
DOI: 10.1007/s00248-019-01438-z
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Rhizospheric Microbial Communities of Native and Alien Plant Species to Cuscuta Parasitism

Abstract: Parasitic plants have major impacts on host fitness. In the case of species of the holoparasitic Cuscuta genus, these impacts were shown to be particularly strong in some invasive alien plants, which has raised interest in the underlying mechanism. We hypothesized that Cuscuta parasitization may exert strong influence in shaping the diversity patterns in the host rhizosphere microbiome and that this may vary between native (coevolved) and alien (non-coevolved) plants. Here, we report on a field study exploring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 101 publications
(105 reference statements)
0
12
0
Order By: Relevance
“…We processed the raw sequences with the DADA2 pipeline (Callahan et al 2016), which is designed to resolve exact biological sequences (Amplicon Sequence Variants [ASVs]) from Illumina sequence data and does not involve sequence clustering (Callahan et al 2017). The detailed process was described in Brunel et al (2019). In short, we removed primers and adapter with the cutadapt package (Martin 2011), merged paired‐end sequences, and removed chimeras.…”
Section: Methodsmentioning
confidence: 99%
“…We processed the raw sequences with the DADA2 pipeline (Callahan et al 2016), which is designed to resolve exact biological sequences (Amplicon Sequence Variants [ASVs]) from Illumina sequence data and does not involve sequence clustering (Callahan et al 2017). The detailed process was described in Brunel et al (2019). In short, we removed primers and adapter with the cutadapt package (Martin 2011), merged paired‐end sequences, and removed chimeras.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown biological invasions can impact the diversity and taxonomical structure of environmental microbiomes. For example, we often see a shift in soil microbiota following invasion by non-native plant species [9][10][11][12][13][14][15][16][17][18][19]. Removal of feral pigs increased the diversity of soil bacterial communities and shifted their structure [20], and invasive crustaceans [21], mussels [22] and jellyfish [23] produce changes in the structure of water microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in soil properties (Table 2 and Fig. 2), litter decomposition (Hobbie, 2015), together with different quantity and quality of root exudations (Sun et al, 2009;Guo et al, 2019;Brunel et al, 2019) are likely the reasons for the different soil microbial community found in Stellera patches. The alpha diversity indices and the rarefaction analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%